Aggression and Juvenile Delinquents - Natarajan, Menaka; Bhuvaneswari, UL (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2021)
Objective: The objective of the study is to find out the effectiveness of eclectic counseling in reducing the aggression level of juvenile delinquents. Method: Aggression scale, developed by Buss and Perry and Biographic datasheet was used for the study. The participants of the study were thirty seven institutionalized juveniles from Tamil Nadu, India. After collecting the demographic details, aggression questionnaire was administered. The responses were scored and tabulated. Eclectic counselling was provided as intervention for a span of three months. Again the data was collected using the same questionnaire. The post-test results were discussed and conclusions were drawn by comparing with pre-test data. Results: The initial results showed that the subjects had a high level of physical aggression, verbal aggression, anger, hostility and overall aggression. The intervention for aggression mainly included relaxation training, self monitoring, reinforcements and group counselling. After three months of intervention, the participants were again assessed and there was a significant reduction in the aggression level of the participants with a t value of 14.774. After intervention, it was found that the level of aggression and its dimensions reduced from high to low except for verbal aggression which fell from high to average. Conclusion: Eclectic counselling helps in the reduction of aggression and the four dimensions of aggression, physical aggression, verbal aggression, anger and hostility, of the juvenile delinquents.How to cite this article:Menaka N, Bhuvaneswari UL. Aggression and Juvenile Delinquents. J Adv Res Psychol Psychother. 2021;4(1&2):1-6.DOI: https://doi.org/10.24321/2581.5822.202101